Pengaruh Pembelajaran Berbasis Proyek Dalam Penerapan Kurikulum Merdeka Terhadap Hasil Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Di SMP Negeri 1 Kraton - Halimah, Siti (AL MURABBI, 2024)
The background of this research is the teacher's new task is to carry out the implementation of the independent curriculum, which is emphasized in the independent curriculum is student creativity, so that in its application the teacher needs to try to be creative. and not monotonous. study process. So far, the teaching and learning process tends to use a monotonous and outdated learning model (lecturing method) with little practice in PAI subjects, so that the willingness and interest of students to learn influences their learning outcomes. To achieve creative and non-monotonous learning, you can implement a project-based learning model. Whereas project-based learning involves students working on projects that can be in the form of individual projects or collaborative projects between groups, so that they can trigger interest in learning, student enthusiasm and can further improve their learning outcomes. the results obtained from the observation of descriptive analysis state that there is a real influence between the project-based learning model and the learning outcomes of Islamic religious education. Based on the inferential statistical analysis, it can be seen that the correlation test and simple linear regression test show a clear effect. between the project-based learning model in implementing the independent curriculum in Islamic religious education with learning outcomes is 24.3% while the remaining 75.7% is due to other factors. The results of the descriptive (qualitative) hypothesis analysis state that the project-based learning model in the implementation of the independent curriculum at Kraton 1 Public Middle School has the ability to increase students' learning desires and creativity so that it influences student learning outcomes in Islamic religious education and morals subjects.The background of this research is the teacher's new task is to carry out the implementation of the independent curriculum, which is emphasized in the independent curriculum is student creativity, so that in its application the teacher needs to try to be creative. and not monotonous. study process. So far, the teaching and learning process tends to use a monotonous and outdated learning model (lecturing method) with little practice in PAI subjects, so that the willingness and interest of students to learn influences their learning outcomes. To achieve creative and non-monotonous learning, you can implement a project-based learning model. Whereas project-based learning involves students working on projects that can be in the form of individual projects or collaborative projects between groups, so that they can trigger interest in learning, student enthusiasm and can further improve their learning outcomes. the results obtained from the observation of descriptive analysis state that there is a real influence between the project-based learning model and the learning outcomes of Islamic religious education. Based on the inferential statistical analysis, it can be seen that the correlation test and simple linear regression test show a clear effect. between the project-based learning model in implementing the independent curriculum in Islamic religious education with learning outcomes is 24.3% while the remaining 75.7% is due to other factors. The results of the descriptive (qualitative) hypothesis analysis state that the project-based learning model in the implementation of the independent curriculum at Kraton 1 Public Middle School has the ability to increase students' learning desires and creativity so that it influences student learning outcomes in Islamic religious education and morals subjects.